WORLD PRACTICE OF THE WATER SECTOR INSTITUTIONAL STRUCTURES IMPROVEMENT - Anatoly Krutov (Водное хозяйство России: проблемы, технологии, управление)
The article discusses the world experience and practice of reforming of the institutional structures involved into water resources management. We present the research outcomes aimed at affirmation of the possibility of the integrated management principles in improvement of the water resources management structures and methods. The researches’ results enabled to formulate regularities and trends in the institutional structures improvement with taking into account experience in application of the water resources integrated management by the countries of different economic and natural/ climatic conditions, as well as different levels of available water supply.